DOI: 10.2969/aspm/06110051
|View full text |Cite
|
Sign up to set email alerts
|

Representation theory of $W$-algebras, II

Abstract: We study the representation theory of the W -algebra W k (ḡ) associated with a simple Lie algebra ḡ at level k. We show that the "−" reduction functor is exact and sends an irreducible module to zero or an irreducible module at any level k ∈ C. Moreover, we show that the character of each irreducible highest weight representation of W k (ḡ) is completely determined by that of the corresponding irreducible highest weight representation of affine Lie algebra g of ḡ. As a consequence we complete (for the "−" redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
141
0
1

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(146 citation statements)
references
References 59 publications
4
141
0
1
Order By: Relevance
“…An alternative construction of W -algebras is also possible using a quantum Hamiltonian reduction based on the works of Feigin and Frenkel [13], Kac et al [25], Kac and Wakimoto [24] and De Sole and Kac [36]. D'Andrea et al [36] and Arakawa [3] have shown that the two definitions of finite W -algebras are equivalent.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…An alternative construction of W -algebras is also possible using a quantum Hamiltonian reduction based on the works of Feigin and Frenkel [13], Kac et al [25], Kac and Wakimoto [24] and De Sole and Kac [36]. D'Andrea et al [36] and Arakawa [3] have shown that the two definitions of finite W -algebras are equivalent.…”
Section: Introductionmentioning
confidence: 98%
“…, p n ) of the diagram's row lengths, where p i is the number of bricks in the i-th row of the pyramid, so that 1 p 1 · · · p n . The figure illustrates the pyramid with columns (1, 3, 4, 2, 1) and rows (1,2,3,5):…”
Section: Introductionmentioning
confidence: 99%
“…These vertex algebras are our main computational tools. 4 In this paper we do not employ the full toolbox available to us in topologically twisted 4d gauge theory. In particular, this toolbox includes topological 3d interfaces (domain walls) and topological 2d surface defects.…”
Section: Overview Of the Gauge Theory Setupmentioning
confidence: 99%
“…Once we achieve that, the general machine of 4d gauge theory dualities will then allow us to construct specific collections of qGL dual twisted D-modules with matching properties 4 The resulting structure is a higher analogue of the structure which arises naturally in the study of 3d…”
Section: Overview Of the Gauge Theory Setupmentioning
confidence: 99%
“…where g is the corresponding simple Lie algebra, W c p (g) is the affine W -algebra associated to g [7,15], and W 0 ( p) Q and W ( p) Q are certain vertex algebras defined below. In the special case of g = s 2 , we recover a more familiar embedding of vertex algebras studied for examples in [2,10,11]:…”
Section: Introductionmentioning
confidence: 99%